Factors affecting early detection behavior of cervical cancer of female sexual workers (FSW) - Regita Nanda Putri; Nanik Setiyawati; Niken Meilani (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2021)
Background: Data of Riskesdas 2018, cancer prevalence in Indonesia showed an increase. The highest prevalence was in Yogyakarta which showed result 4,8/1000 population. New cervical cancer cases in Yogyakarta ranked second. The different prevalence of HPV between female sexual workers (FSW) and general population was 42,7%, higher than the general population. Objective: This study aims to determine the factors that influence the early detection of cervical cancer in FSW in Gedongtengen Public Health Center Area in 2020. Methods: This research used an observational analytic with cross sectional approach. The research subjects were 40 female sexual workers (FSW) in Gedongtengen Public Health Center area, with the data technique taken was random sampling technique. The research instrument was a questionnaire. Data analysis used Chi-square test, Fisher exact test, and logistic regression. Results: Variables associated with early detection behavior of cervical cancer were knowledge (p-value=0,001), attitude (p-value=0,008), and access to information (p-value =0,006). While age (p-value=0,705), education (p-value=0,510), income (p-value=0,709), length of work (p-value=0,642), and age at first sexual intercourse (p-value=0,594) were not related to early detection of cervical cancer. The most influential factor was attitude (OR=20,598) CI 95% (2,585-164,110). Conclusion: Factors affecting early detection behavior of cervical cancer were knowledge, attitudes, and access to information. The dominant factor was attitude of the respondent.